Correlation between Dietary Inflammatory Index (DII) and Neck Circumference (NC) in Coronary Artery Disease Patients - Elahe Shamshirgardi; Fatemeh Najafitirehshabankareh; Neda Haghighat; Nitin Shivappa; James R. Hebert; Maedeh Jabbari; Yalda Mortazavi; Laya Saeid; Zahra Shamekhi (Shiraz University of Medical Sciences, 2022)
Background : Inflammation, a risk factor for cardiovascular disease (CVD), is affected by diet.Dietary inflammatory index (DII) is used to determine inflammation of diet. In addition, Neck circumference (NC), an indicator for upper-body subcutaneous adipose tissue distribution, is related to cardiovascular risk factors. This study aimed to examine the correlation between DII and NC in a nationally representative sample case and control. Methods: In this cross-sectional study, the case group was chronic heart disease patients hospitalized in Al-Zahra Heart Clinic, Shiraz, Iran (N = 100). The Control group did not suffer from any heart-related diseases. Dietary intake data were determined using a single interview and food frequency questionnaire (FFQ). NC was assessed using standard methods. Nutritionist-4 software was used to analyze nutrient intakes from FFQ. The method of Shivappa et al. was used to calculate DII. Results: The mean of NC in the case and control group were 39.09±4.18 and 36.68±4.32 cm. The mean of DII in the case and control groups were -0.018±1.53 and 0.40±155. There was no significant difference between the DII score of the case and control groups (p:0.056, t:-1.922). No significant correlation was observed between DII score and NC in the case(p:0.750,r:0.032) and control(p:0.294,r:0.106) groups. Conclusion: There was no correlation between DII score as a risk factor for CVD and NC in both case and control groups.